Topical Mitomycin-C versus Subconjunctival 5-Fluorouracil for Management of Bleb Failure - Pakravan, Mohammad (Ophthalmic Research Center, 2011)
PURPOSE: To compare the efficacy and safety of topical mitomycin-C (MMC) drops with that of subconjunctival 5-fluorouracil (5-FU) injections for management of early bleb failure after trabeculectomy or combined phacoemulsification and trabeculectomy with posterior chamber intraocular lens implantation (PT+PCIOL). METHODS: In a randomized comparative study, 37 eyes of 37 patients with impending early bleb failure received MMC 0.02% eye drops for 2 or 4 weeks (19 eyes) or subconjunctival 5-FU injections, 5 mg per dose (18 eyes). Complete success was defined as 5 < IOP ≤ 18 mmHg without medications. RESULTS: Baseline characteristics were comparable between the study groups. However, there were more cases of combined PT+PCIOL in the MMC group [11 (57.9%) eyes versus 3 (16.7%) eyes, P = 0.017]. Mean preoperative IOP was 20.5±8.85 mmHg in the MMC group and 25.82±11.35 mmHg in the 5-FU group (P = 0.129), which was decreased to 13.2±6.1 and 10.6±4.8 mmHg respectively after 12 months (P = 0.159). There was no significant difference between the study groups in terms of bleb extent (P = 0.170), height (P = 0.178) or vascularity (P = 0.366). At the end of the study, complete success was achieved in 13 eyes (68.4%) in the MMC group and 14 eyes (77.8%) in the 5-FU group (P = 0.714). The survival of success at 8 months (median follow-up) was 89.5% and 86.5% in the MMC and 5-FU groups respectively; the number of glaucoma medications (P = 0.707) and best-corrected visual acuity (P = 0.550) were also comparable. Complication rates were similar in the study groups (P = 0.140). CONCLUSION: Topical MMC 0.02% has comparable safety and efficacy to subconjunctival 5-FU injections for management of early bleb failure. Topical MMC 0.02% drops are more convenient and can be initiated first, while 5-FU injections may be reserved for eyes with an insufficient response to topical MMC.